Arquivos Universitários: a gestão eficaz e a preservação digital. Um estudo dos sistemas acadêmicos e de recursos humanos da Universidade Federal de Minas Gerais-UFMG - Silvana Aparecida Silva dos Santos (2018)
This study's goal is to make known and characterize Federal University of Minas Geraiss (UFMG) informational systems, specifically, those of academic and Human Resources natures, implanted and being used by the Institution. The perception and opinion about the preservation of digital and electronic produced of the staff responsible for the construction and use of these systems was ascertained by the means of a non-structured interview. The background for this research was the theoretical instrumental of archival studies. The acomplishment of this paper came from the assumption of the academical archives' relevance for the development of the university's assignments and competences. The archives' importance is widely known, however, there is little value given to them as a strategical tool in the institutional structure. There is no management of the documents in its production phase and effective use; therefore, there is not a definition of the resources and politics to attend the problems and its complexity. These issues are even more visible and complex when mentioning the management and preservation of digital and electronic documents. Based on this approach, the current research intended to make known the academic and human resources systems implanted at the university, its polysemy, characteristics, and interaction with the production and organization processes of the academical archives.